2016
DOI: 10.3390/polym8100356
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Crystallinity on Compressive Properties of Al-PTFE

Abstract: Al-PTFE (Al-polytetrafluoroethene) is an important kind of Reactive Material (RM), however only limited importance was placed to the effect of crystallinity of PTFE on the mechanical and reactive behavior. This paper investigated the influence of crystallinity on the compression behavior of Al-PTFE at strain rates range from 10 −2 to 3 × 10 3 s −1 . Two kinds of samples were prepared by different sintering procedures to acquire different crystallinity. The samples' crystallinity was characterized by the densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…When the impact velocity is moderate such as in drop weight tests and in SHPB tests, fracture-induced hot-spots are also crucial to the ignition process for Al-PTFE. It was found that the first signs of reaction could only be observed in cracks of samples in drop weight tests (impact velocity 1 m/s~10 m/s) [25] and in SHPB tests (impact velocity 20 m/s~30 m/s) [26].…”
Section: The Applicability Of the Crack-induced Hot-spots Generation mentioning
confidence: 99%
“…When the impact velocity is moderate such as in drop weight tests and in SHPB tests, fracture-induced hot-spots are also crucial to the ignition process for Al-PTFE. It was found that the first signs of reaction could only be observed in cracks of samples in drop weight tests (impact velocity 1 m/s~10 m/s) [25] and in SHPB tests (impact velocity 20 m/s~30 m/s) [26].…”
Section: The Applicability Of the Crack-induced Hot-spots Generation mentioning
confidence: 99%
“…Such a perspective is valid for the material subjected to roller compaction. However, it has been reported that a reduction in the true density of a material can take place when the structure undergoes a polymorphic transformation [40,41]. In this regard, changes in the molecular arrangement of a powder can result in loose packing at the particulate level.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the samples were put into a furnace to undergo a sintering cycle under the protection of argon atmosphere. Different from the sintering processes in published researches, the maximum temperature in our sintering process was much lower while the sintering cycle was much shorter to achieve a more brittle material property [6,17,22]. Specifically, it included heating the pressed samples at a rate of about 50 °C per hour to a final temperature of 300 °C, holding at the final temperature for 6 h, and then cooling to room temperature at the rate of 50 °C per hour.…”
Section: Methodsmentioning
confidence: 96%